The Alignment of Accounting Curriculum with Market Requirements: The Iraqi Case - Ramadhan, Sherzad; Walid, Aridah Mamoun; Alkoutaini, Hasan; Ahmed, Fareeba; Khorsheed, Hariwan; Obaied, Shmal; Amar, Aldulaimi (European Scientific Journal, ESJ, 2024)
This research investigates at how Iraqi university accounting courses connect to industry demands in an effort to raise the standard and relevance of accounting education. The study used a survey with a questionnaire that was distributed to teachers, graduates, employers, and professionals in the accounting area in Iraq. The study looks at the most recent accounting curriculum, demographic data, relevance ratings for accounting courses, and assessments of essential work skills. The study showed a wide range of demographics, including notable responses from academics (58%), and employers (51%). Results show areas of convergence and divergence in the perceived importance of specific accounting courses, which may indicate gaps between theoretical ideas and practical implementations. Crucial skills and non-accounting courses share some shared aims and small differences as well. The report highlights how important it is to align Iraq’s accounting curriculum with business needs. The proposals include systematic curriculum assessments, more industry-academia collaboration, continual professional development for educators, and an emphasis on a broader range of abilities. In response to shifting market needs, the paper makes evidence-based suggestions for enhancing accounting education in Iraq.